Adult population fluctuation of Oriental fruit moth, Grapholita molesta (Lep.: Tortricidae), in peach orchards of Ãanakkale, Turkey - A. K¸rºat ™ahin; İ. Ãzbek; A. KÃ¼rÅat Åahin (نامه انجمن حشره‌شناسی ایران, 2014)
The study was conducted in nine different peach orchards in Central district, Lapseki and Bayramiç districts of Çanakkale Province. In this study, adult population change of Oriental fruit moth, (Grapholita molesta Busck, 1916, Lepidoptera: Tortricidae) was determined with pheromone traps. At the end of the study it was observed that G. Molesta is abundant in all sampling orchards in both two years. Even though adult emergence changes at different years, it was started at mid April and continued until the end of November. Four-five flight periods were determined at the months of April, June, July, August and October throughout the season. When adult population development curves were examined, it was determined that the pest could generate four-five generation per year related to daily temperature values of early spring. It was concluded that late cultivars would be more affected because of the high amounts of adults in August and September.